2020
DOI: 10.1155/2020/1307232
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Risk Factors for Recurrent Erysipelas and Cellulitis of the Lower Limb: A Cross-Sectional Study of Epidemiological Characteristics of Patients Hospitalized due to Skin and Soft-Tissue Infections

Abstract: Background. Erysipelas and cellulitis are common, acute, bacterial infections of the skin and subcutaneous tissue. The incidence of these infections is growing, and the recurrence rate is high. Effective antibiotic prophylaxis is available, but insufficient data exist on the risks factors for recurrent infection. Purpose. To compare comorbidities and laboratory findings in patients with single-episode and recurrent erysipelas/cellulitis in order to identify risk factors for recurrent erysipelas/cellulitis. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Risk factors for single episodes are associated with trauma, wounds or environmental exposure that are unlikely to recur. 18 , 30 Risk factors which are not modifiable or managed appropriately are more frequently associated with recurrent cellulitis.…”
Section: Risk Factors For Recurrent Cellulitismentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for single episodes are associated with trauma, wounds or environmental exposure that are unlikely to recur. 18 , 30 Risk factors which are not modifiable or managed appropriately are more frequently associated with recurrent cellulitis.…”
Section: Risk Factors For Recurrent Cellulitismentioning
confidence: 99%
“… 11 , 16 One study found a higher recurrence of cellulitis in the tibial region as compared to the femoral region or the foot. 11 Other risk factors that were identified include peripheral vascular disease, 13 , 17 chronic kidney disease, 17 chronic obstructive pulmonary disease, 13 , 30 and liver disease. 13 Social factors associated with the other established risk factors are also important, particularly homelessness which can be linked to poor skin and general health care.…”
Section: Risk Factors For Recurrent Cellulitismentioning
confidence: 99%
“…Hinsichtlich anderer Erkrankungen wie Diabetes mellitus, peripherer arterieller Verschlusskrankheit, Malignomen und chronisch-obstruktive Lungenerkrankung sind die Studienergebnisse kontroversiell hinsichtlich ihrer Eigenschaft als Risikofaktoren, die die Entstehung eines Erysipels möglicherweise begünstigen. Kontroversen bestehen ebenso hinsichtlich einer Adipositas als Risikofaktor [12,[23][24][25][26][27][28][29].…”
Section: Risikofaktorenunclassified
“…Another study by Inghammar et al 24 has shown that lymphedema is the greatest risk factor for erysipelas recurrence, which is in accordance with results from more recent research. 25 It has also been shown that late-stage lymphedema correlates with a higher incidence of erysipelas 26 and that lymphedema is a risk factor for developing bacteremia in the presence of cellulitis. 27 In a study by Deng et al, 20 patients with LEL had an increased OR of 2.53 (95% CI: 1.77–3.62) for developing skin infections compared with patients with upper extremity lymphedema (UEL).…”
Section: Introductionmentioning
confidence: 99%